2015
DOI: 10.1155/2015/654046
|View full text |Cite
|
Sign up to set email alerts
|

Waist-to-Hip Ratio, but Not Body Mass Index, Is Associated with Testosterone and Estradiol Concentrations in Young Women

Abstract: We studied if testosterone and estradiol concentrations are associated with specific female waist-to-hip ratios (WHRs) and body mass indices (BMIs). Participants were 187 young women from which waist, hips, weight, and height were measured. In addition, participants informed on which day of their menstrual cycle they were and provided a 6 mL saliva sample. Ninety-one of them were in the follicular phase and 96 in the luteal phase. Only in the fertile phase of the menstrual cycle we found a significant interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 44 publications
1
22
0
1
Order By: Relevance
“…We collected three physical features hypothesized to be linked to women's immediate fertility: the waist‐to‐hip ratio (the ratio between body circumference at the waist and the hips or WHR, Singh, ; Jasienska et al ., ; Singh & Randall, ; Lassek & Gaulin, ; Mondragón‐Ceballos et al ., ; Butovskaya et al ., ; but see Nenko & Jasienska, ), the fundamental frequency of the voice (F0, Harries et al ., ; Abitbol et al ., ; Feinberg, ; Evans et al ., ; Abend et al ., ) and the facial femininity (Farkas, ; Johnston & Franklin, ; Perrett et al ., ; Fink & Neave, ; Law Smith et al ., ; Little et al ., ; Pfluger et al ., ; Jones, ). The WHR was measured in the laboratory by the investigator.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We collected three physical features hypothesized to be linked to women's immediate fertility: the waist‐to‐hip ratio (the ratio between body circumference at the waist and the hips or WHR, Singh, ; Jasienska et al ., ; Singh & Randall, ; Lassek & Gaulin, ; Mondragón‐Ceballos et al ., ; Butovskaya et al ., ; but see Nenko & Jasienska, ), the fundamental frequency of the voice (F0, Harries et al ., ; Abitbol et al ., ; Feinberg, ; Evans et al ., ; Abend et al ., ) and the facial femininity (Farkas, ; Johnston & Franklin, ; Perrett et al ., ; Fink & Neave, ; Law Smith et al ., ; Little et al ., ; Pfluger et al ., ; Jones, ). The WHR was measured in the laboratory by the investigator.…”
Section: Methodsmentioning
confidence: 99%
“…Cues of immediate fertility can be found in body shape, voice pitch or facial features; in fact, all traits linked to sexual maturity, age and parity or substantially influenced by sex hormones (which are factors influencing immediate fertility) have the potential to influence physical attractiveness (see, e.g. Symons, ; Henss, ; Singh, ; Jasienska et al ., ; Feinberg et al ., ; Law Smith et al ., ; Pipitone & Gallup, ; Singh et al ., ; Little et al ., ; Puts et al ., , ; Pfluger et al ., ; Jones, ; Mondragón‐Ceballos et al ., ; Sugiyama, ; Butovskaya et al ., but see Marcinkowska et al ., , for some modulations of these preferences). To increase their reproductive success, males should prefer females of the age at which age‐specific fertility peaks, at least for short‐term mates (Maestripieri et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have indicated that female waist-to-hip ratio, or WHR, is inversely related to various objective parameters: smaller WHR (i.e. more hourglass-like body figure) indicates higher levels of sex hormones such as estradiol and its precursor testosterone (DeRidder et al, 1990;Mondragón-Ceballos, García Granados, Cerda-Molina, Chavira-Ramírez, & Hernández-López, 2015), smaller health risk (Björntorp, 1991;Folsom et al, 1993;Misra & Vikram, 2003), and a greater availability of fat resources needed for successful fetal brain development (Lassek & Gaulin, 2006. Even though WHR is being used as a unique measure, the waist and hip are associated with different aspects of female health.…”
Section: Waist-to-hip Ratio (Whr)mentioning
confidence: 99%
“…In a sexual-selection evolutionist framework, perceiving a static female body vs. a dynamic male body may boost the salience of gender-typing physical traits, such as WHR for women and muscularity for men. Numerous studies, indeed, have shown that a female body is strongly defined by the WHR, since it appears to be related to objective gender-specific qualities such as the levels of sex hormones (e.g., estradiol;De Ridder et al, 1990;Mondragón-Ceballos et al, 2015), the accessibility to fat resources suitable for fetal neurodevelopment (Lassek and Gaulin, 2008), and the more general capacity to sustain pregnancy (Singh, 1993). Obviously, WHR might only serve as a proxy for covariating bodily traits that shape the entire body phenotype and co-determine the judgment of body attractiveness (Brooks et al, 2015).…”
Section: Discussionmentioning
confidence: 99%